Reductive aromatization of oxindoles to 3-substituted indoles. Issue 28 (9th July 2020) - Mandal, Tirtha; Chakraborti, Gargi; Dash, Jyotirmayee
Graphical abstract: Highlights: Practical and scalable synthetic route to 3-indoles. Partial reduction-aromatization of oxindoles to 3-indoles using LiAlH4 . The reaction proceeds via an indolinium ion intermediate. Synthesis of a diverse class of 3-indoles and bis-indoles. A quick access to tryptamine. Abstract: A practical and scalable approach for the synthesis of 3-substituted indoles is delineated via hydride nucleophilic addition to 3-substituted-2-oxindoles. The reaction proceeds through reductive aromatization involving indolinium ion intermediate. A wide range of 3-functionalized indoles have been synthesized. The method is employed for the synthesis of 3, 3ʹ-bis-indoles and a dimeric 3-indole derivative. Moreover, this protocol is used to obtain naturally occuring amino acid tryptamine.